2023
DOI: 10.1002/jsfa.12463
|View full text |Cite
|
Sign up to set email alerts
|

Edible coating enriched with cinnamon oil reduces the oxidative stress and improves the quality of strawberry fruit stored at room temperature

Abstract: BACKGROUND The present study aimed to assess the impact of a starch/gelatine coating containing cinnamon oil on selected quality attributes and redox status in strawberry fruit stored at room temperature (72 h). RESULTS Research showed that the application of cinnamon oil to an edible coating allows an improvement of the quality of strawberry fruit stored at room temperature. The cinnamon oil coating inhibits the development of yeast and mould, and reduces loss of soluble solids and ascorbic acid during 72 h s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…In the current study, background microorganisms of fresh-cut potatoes in the AEC-TEO treatments were lower than those in the control, and it is reasonable to suggest that TEO exhibits antibacterial activity and that the coating process itself might wash away some microorganisms. Other research showed that an edible coating containing cinnamon oil inhibited yeast and mold on strawberries [28]. An alginate edible coating with thyme oil reduced mold and yeast growth compared to the control and alginate without thyme oil [57].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the current study, background microorganisms of fresh-cut potatoes in the AEC-TEO treatments were lower than those in the control, and it is reasonable to suggest that TEO exhibits antibacterial activity and that the coating process itself might wash away some microorganisms. Other research showed that an edible coating containing cinnamon oil inhibited yeast and mold on strawberries [28]. An alginate edible coating with thyme oil reduced mold and yeast growth compared to the control and alginate without thyme oil [57].…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, TEO might be combined with EC to reduce these negative impacts. The preservation effects of alginate EC with oregano essential oils, carboxymethyl chitosan-pullulan EC with galangal essential oil, EC with cinnamon essential oil, and alginate-based EC with thyme essential oil have all been evaluated on fruits and vegetables such as tomatoes, mangos, strawberries, and cantaloupes [26][27][28][29]. Moreover, the quality and safety of fresh-cut potatoes treated with alginate-based EC containing thyme essential oil have been not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on developing active coatings, blending biopolymers with molecules with antimicrobial and antioxidant properties such as grape seed extracts [106], apple peel polyphenols [107], essential oils [114, 115] and Aloe vera gel [122]. Furthermore, these coatings can reduce respiration rate, transpiration rate (weight loss), colour change and fruit firmness modification, as well as ascorbic acid, the total content of phenols and anthocyanin degradation (Table 3).…”
Section: Packaging Technologies Used To Extent Strawberry Shelf Lifementioning
confidence: 99%